BCCT Model Preparation Center Learning Supporting Children's Readiness for School - Tjutju Herawati; Sukiman Sukiman (Jurnal Studi Guru dan Pembelajaran, 2024)
The urgency of this research lies in the lack of enthusiasm among young children to start learning, which is partly caused by a lack of innovation in teaching methods. This issue is particularly crucial as early childhood is a critical period for cognitive development. This classroom action research aims to develop the potential of kindergarten group B children in readiness to enter elementary school. In this increase, children will be directed to learn using the Preparation Center with the BCCT model and the Bosowa School integrated curriculum. This research is focused on supporting children's school readiness, especially in pre-numeracy, pre-reading and pre-writing. Classroom Action Research (PTK) will be carried out in 2 cycles, each cycle consisting of planning, implementation, observation and reflection. Then the results of the investigation will be continued with an evaluation at the end of the lesson. Learning outcome data was obtained from learning outcome evaluation tests at the preparation stage for children's school readiness. This research involved Kindergarten B, totaling 59 children. The reference for assessing children's observations uses a Likert scale. The results of the research showed that there was an increase in cycle II in the pre-numeracy aspect, 77.8%, pre-reading, 72.6%, and pre-writing, 74%. So the data obtained with an average of >70% complete results, and the use of preparation centers with the BCCT model can support school readiness.